Information Disclosure and the Peer Effect of Corporate Technology Innovation - Yang, Xinyao; Shi, Zheng; Li, Chengxing (Transformations In Business & Economics, 2024)
Information disclosure is an essential means to improve the effectiveness of the capital market. How to promote capital market development by perfecting the information disclosure system is constantly an important topic of the supervision department and academic circle. To discuss the profound effects of information disclosure on enterprises in the capital market, based on information theory and dynamic competition theory, using the data of 1158 Chinese listed enterprises on the growth enterprise market (GEM) from 2009 to 2022, the influences of information disclosure on peer effect of corporate technology innovation were explored through multivariate regression method. Results show that information disclosure can strengthen the peer effect of corporate technology innovation, which may be further intensified with the increasing enrichment of information disclosure paths and contents.The registration system reform policy implemented in China’s GEM in 2020 could promote the peer effect of corporate technology innovation. While enterprises with poorer external and internal information environmental transparency are benefiting from the positive effects of increased information disclosure degree, increasing information disclosure degree has strong competitive influences on the peer effect of technology innovation of enterprises. Conclusions not only provide some causal references to the promotion of information disclosure on the peer effect of technology innovation but also verify the policy effect of registration system reform in GEM and disclose the important role of China’s registration system reform in improving resource allocation efficiency of capital markets.
Keywords: peer effects; information disclosure; technology innovation; GEM; registration system